Feasibility of Novel Magnetically Controlled Cable Capsule Endoscopy System In Vitro Experiments for Gastric Examination - Yaoping Zhang; Lina Qu; Yani Gou; Jinyong Hao; Xiaojun Huang (Gastroenterology Research and Practice)
Background. Magnetically controlled capsule endoscopy has been shown to be feasible for the examination of gastric diseases. However, there may be problems, such as low image quality, incomplete esophageal observation, and capsule retention. We developed a novel magnetically controlled cable capsule endoscopy (MCCCE) system and evaluated its feasibility through in vitro experiments. Methods. Three experienced endoscopists performed MCCCE on the plastic stomach model and the excised porcine stomach model 5 times, respectively. Outcomes included handle ability, examination time, examination completion, and image quality. The examination completion was accessed by other two blinded endoscopists, and the image quality was compared with conventional gastroscopy (Olympus, GIF-290). Results. The performance of MCCCE in vitro experiments is excellent, with a mean operation time of 18.5 minutes in the plastic stomach model and 17.3 minutes in the excised porcine stomach model. The visualization rate of the gastric mucosa is >90% in the plastic stomach model and 75–90% in the excised porcine stomach model. The images of MCCCE are very clear, with good color resolution and no image distortion, which seem to be comparable to conventional gastroscopy. Conclusions. MCCCE system is feasible for gastric examination in vitro experiments, living animal experiments and human trials need to be further conducted.